Electronic coaching and training records in athletics - Kuntze, G.; Cheng, L.; Austin, T.; Nguyen, D.; Karla, D.; Kerwin, D. G.; Hailes, S. (Sportinformatik trifft Sporttechnologie. Tagung der dvs-Sektion Sportinformatik und der deutschen interdisziplinären Vereinigung für Sporttechnologie vom 15.-17. September in Darmstadt. Abstracts, 2011)
Technology assisted performance monitoring affords novel opportunities for tracking and guiding training programs and the development of elite as well as recreational athletes. Comprehensive training diaries are kept by athletes and coaches and coaching records are forming a prerequisite for funding allocation by for example, track and field athletics in the United Kingdom (uk sport, 2009). Sprinting is a highly technical discipline involving multiple parameters that may be recorded for athlete monitoring and the task of longitudinal record keeping becomes ever more complex. Automation of this process, currently witnessed for example in the medical field, is a useful tool for managing data and relieving the coach and athlete from some record keeping tasks. As part of the SESAME project (Sensing for Sport and Managed Exercise, http://www.sesame.ucl.ac.uk/) an integrated system has been developed with the aim of providing fine grained athlete performance information including split times, step frequency, step length, etc. A series of interviews with leading sprints coaches (Thompson, Bezodis, & Jones, 2009) revealed the importance of accurate and sport specific performance data, where longitudinal records may provide reliable assessments of athlete development and coaching practices, using specific historical points of reference. PLG (Pisa Light Gates) is a novel multilane light gate system (Cheng et al., 2010), providing accurate 10 m split time and velocity readings for 5 lanes of a 60 m indoor running track, and forms the backbone of the integrated system. PLG is operated wirelessly, requires no equipment setup and allows multiple athletes to be tracked simultaneously at the press of a button. Following a run, all data are displayed in realtime on a WiFi device (iPod Touch, Apple Inc.) and importantly all data are logged automatically and stored on a remote server permanently for interrogation by the coach after a training session. In this abstract we cover the development and application of an automated performance parameter databasing system which is fully integrated with PLG. This system has been developed with continuous feedback from coaches and athletes and is being used by athletics coaches on a daily basis at an indoor athletics centre.